MAIN SOCIO-PSYCHOLOGICAL PROBLEMS OF MODERN SOCIETY: ANALYSIS, WAYS OF SOLUTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article examines the role of personality in the formation of a culture of health and ensuring mental well-being, the importance of knowing the structure of personal interactions in society. Correlation of individual-typological personality characteristics, spheres of personality structure and somatic aspects of life activity can be predictors of burnout syndrome, predisposing risk factors of the disease in modern society.